Applying the Limited Liability Principles: Fiduciary Duties and Accountability of Limited Liability Company Director - Muarif, Anwarul (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2024)
The accountability of the board of directors as an organ that holds a fundamental role in the management of a limited liability company is based on the obligations of fiduciary duties and fiduciary of care. A limited liability company is a legal entity that employs the basic concept of limited liability as a means of accountability. This principle also applies to the accountability of the board of directors. Actions taken by the board of directors in managing the company will be considered as actions of the company itself, and the company will be responsible for the consequences of these actions as long as they do not contradict the company’s Articles of Association and are not due to the negligence or fault of the directors. The principle of limited liability may not apply if, in the execution of their fiduciary duties and fiduciary of care, the directors commit ultra vires acts, pierce the corporate veil, or act contrary to the Business Judgment Rule. The Business Judgment Rule is a principle that can protect the directors from personal liability if the management actions or business decisions they make result in harm to the company. The concept of limited liability in Indonesia is regulated in Article 7 of Law Number 40 of 2007 concerning Limited Liability Companies. Directors will be exempted from personal liability for their actions in running the company as long as it is based on the Company's Articles of Association/Bylaws and not due to negligence and errors of the directors. If the company experiences losses, the directors can be held personally liable if it is proven that the losses were caused by actions that are not in accordance with the Articles of Association/Bylaws and meet the elements of negligence, bad faith, carelessness, conflict of interest and absence of preventive measures.